Metagenomic Survey of the Highly Polyphagous Anastrepha ludens Developing in Ancestral and Exotic Hosts Reveals the Lack of a Stable Microbiota in Larvae and the Strong Influence of Metamorphosis on Adult Gut Microbiota - Aluja, Martín; Zamora-Briseño, Jesús Alejandro; Pérez-Brocal, Vicente; Altúzar-Molina, Alma; Guillén, Larissa; Desgarennes, Damaris; Vázquez-Rosas-Landa, Mirna; Ibarra-Laclette, Enrique; Alonso-Sánchez, Alexandro G.; Moya, Andrés (Frontiers in Microbiology, 2021)
We studied the microbiota of a highly polyphagous insect, Anastrepha ludens (Diptera: Tephritidae), developing in six of its hosts, including two ancestral (Casimiroa edulis and C. greggii), three exotic (Mangifera indica cv. Ataulfo, Prunus persica cv. Criollo and Citrus x aurantium) and one occasional host (Capsicum pubescens cv. Manzano), that is only used when extreme drought conditions limit fruiting by the common hosts. One of the exotic hosts (“criollo” peach) is rife with polyphenols and the occasional host with capsaicinoids exerting high fitness costs on the larvae. We pursued the following questions: (1) How is the microbial composition of the larval food related to the composition of the larval and adult microbiota, and what does this tell us about transience and stability of this species’ gut microbiota? (2) How does metamorphosis affect the adult microbiota? We surveyed the microbiota of the pulp of each host fruit, as well as the gut microbiota of larvae and adult flies and found that the gut of A. ludens larvae lacks a stable microbiota, since it was invariably associated with the composition of the pulp microbiota of the host plant species studied and was also different from the microbiota of adult flies indicating that metamorphosis filters out much of the microbiota present in larvae. The microbiota of adult males and females was similar between them, independent of host plant and was dominated by bacteria within the Enterobacteriaceae. We found that in the case of the “toxic” occasional host C. pubescens the microbiota is enriched in potentially deleterious genera that were much less abundant in the other hosts. In contrast, the pulp of the ancestral host C. edulis is enriched in several bacterial groups that can be beneficial for larval development. We also report for the first time the presence of bacteria within the Arcobacteraceae family in the gut microbiota of A. ludens stemming from C. edulis. Based on our findings, we conclude that changes in the food-associated microbiota dictate major changes in the larval microbiota, suggesting that most larval gut microbiota is originated from the food.